2022
DOI: 10.1111/ddi.13654
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the impacts of multiple stressors on the decline in kelps along the coast of Victoria, Australia

Abstract: Aim: Kelp forests throughout temperate regions of the world serve as foundation species that play a critical role in sustaining the health and function of marine ecosystems but are experiencing declines in abundance due to a loss in resilience as the ocean climate changes. Ocean warming along southeast Australia has already been linked to dramatic losses of kelp species and is contributing to the range expansion and population increases of two species of sea urchin. This research attempts to understand the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…Therefore, dolphins may prefer to forage in less dense seagrass patches (Mann et al., 2021) or on the edge of seagrass beds, in transitional zones (Allen et al., 2001; Nowacek, 2005), where acoustic detection of prey is more efficient. Infralittoral reefs are key habitats for many fish species because they can provide a source of food and shelter (Davis et al., 2020; Young et al., 2022). Anderson (2003) also found that sand‐associated fish species such as sand flatheads were more common in close proximity to structured rather than completely unvegetated habitats, which further supports findings from Ferrell and Bell (1991) that non‐seagrass fish species are more abundant in sand within 10 m of seagrass (Smith et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, dolphins may prefer to forage in less dense seagrass patches (Mann et al., 2021) or on the edge of seagrass beds, in transitional zones (Allen et al., 2001; Nowacek, 2005), where acoustic detection of prey is more efficient. Infralittoral reefs are key habitats for many fish species because they can provide a source of food and shelter (Davis et al., 2020; Young et al., 2022). Anderson (2003) also found that sand‐associated fish species such as sand flatheads were more common in close proximity to structured rather than completely unvegetated habitats, which further supports findings from Ferrell and Bell (1991) that non‐seagrass fish species are more abundant in sand within 10 m of seagrass (Smith et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…where acoustic detection of prey is more efficient. Infralittoral reefs are key habitats for many fish species because they can provide a source of food and shelter (Davis et al, 2020;Young et al, 2022).…”
Section: Oceanographic Drivers Of Distribution Across Port Phillip Baymentioning
confidence: 99%
“…Although no relationship between temperature and morphology was found, increases in temperature may still impact the effectiveness of morphological adaptations to other stressors. Thermal stress is known to increase tissue fragmentation in kelps (Simonson et al, 2015), therefore increased temperatures may restrict the effectiveness of morphological responses to drag stress , Young et al, 2023. It is also likely that the extent to which such multi-stressor effects will impact Australasian E. radiata will vary across existing environmental gradients.…”
Section: Regional Morphological Variation Across Australasiamentioning
confidence: 99%
“…The success of E. radiata across its geographical range, and its function as a habitat modifier, is likely related to the species ability to morphologically acclimate to a wide variety of environmental conditions. Despite this, the effects of climate change are already pushing some populations past thresholds where morphological acclimation is effective (Young et al, 2023). Greater synthesis and understanding of the existing variability in E. radiata morphology is therefore of pertinence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the gametophyte life stage displays evidence of acclimatization or adaptation to local thermal regimes, with higher thermal optima positively correlated with higher in situ temperatures [41]. Recent modelling work by Young et al [42] demonstrated the potential for declines in E. radiata cover in cool-edge populations of the southeastern Australian state of Victoria, with one of the main drivers being increased sea surface temperatures. However, there is little understanding of the thermal tolerance of E. radiata sporophytes at the physiological level from populations at the cool edge of its distribution, and no studies have assessed whether thermal performance is likely to change with the elevated levels of CO 2 projected under global ocean change.…”
Section: Introductionmentioning
confidence: 99%